Legal Protection for Winners of Land Rights Auctions That Are the Object of Dispute in Court Cases - Adhitya, Bakhtiar Satria; Hafidz, Jawade (Sultan Agung Notary Law Review, 2024)
This study aims to analyze: 1) Legal implications for the implementation of land rights auctions that are still the object of dispute in cases in court. 2) Legal protection for winners of land rights auctions that are the object of dispute in cases in court. The approach method used in this study is a qualitative approach. This type of research is empirical research. The types and sources of data in this study are primary data obtained through interviews and secondary data obtained from literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) Legal implications for the implementation of land rights auctions that are still the object of dispute in cases in court can include several complex aspects, namely legal uncertainty of land rights, difficulty in obtaining absolute ownership, potential financial losses, obligations to resolve potential further disputes, and the influence of court decisions. Court decisions related to auction results will greatly affect the legal certainty of auction winners, because the filing of lawsuits by other parties after the auction affects the validity of the ownership rights obtained. If the court provides clear certainty regarding land ownership to the auction winner, this will strengthen its legal certainty. However, if there is still uncertainty or disputes regarding ownership, legal certainty can continue to be questioned. 2) Legal protection for the winner of the auction of land rights that are the object of dispute in a case in court, namely: If another party files a lawsuit against the auction object, then the court decides that the auction is legally valid, then in this case the auction winner's rights to the auction object already have permanent legal force and can no longer be challenged by any party. If there is a lawsuit and then the court decides that the auction is void because there is an element of an unlawful act, then the legal protection obtained by the auction winner is to be able to claim back the purchase money for the auction object that has been paid.